Tailored therapies for primary immunodeficiencies - Cinicola, Bianca; Pulvirenti , Federica; Brindisi, Giulia; Marseglia, Gian Luigi; Castagnoli, Riccardo; Foiadelli, Thomas; Caffarelli, Carlo; Licari, Amelia; Miraglia Del Giudice , Michele; Zicari, Anna Maria; Duse , Marzia; Cardinale, Fabio (Acta Biomedica Atenei Parmensis, 2021)
Primary immunodeficiency disorders (PIDs) are rare inherited monogenic disorders of the immune system, characterized by an increased risk of infection, immune dysregulation and malignancies. To date, more than 420 PIDs have been identified. The recent introduction of high throughput sequencing technologies has led to identifying the molecular basis of the underlying aberrant immune pathway, and candidate targets to develop precision treatment, aimed at modifying the clinical course of the disease. In PID, targeted therapies are especially effective to manage immune dysregulation and autoimmunity, also reducing the incidence of side effects compared to conventional treatments, sparing the use of steroids and immunosuppressive drugs. Moreover, in the last years, the approach of conventional treatments such as immunoglobulin replacement therapies has evolved and the indication has expanded to new diseases, leading to individualized strategies to both improve infection control and quality of life. Similarly, the new advent of gene therapy in selected PIDs has introduced the benefit to correct the immunological defect, reducing at the same time the complications related to the hematopoietic stem cell transplantation. Here, we illustrate the most recent findings on tailored treatments for PIDs.